The Rational Nonpurchase of Long-Term-Care Insurance - Pauly, Mark V. (Journal of Political Economy, 1990)
Only a tiny fraction of the nonpoor population currently purchases private insurance coverage against long-term-care (LTC) costs. Studies generally attribute the failure to purchase private coverage to "unawareness" by potential purchasers of the benefits of coverage and a misperception that Medicare currently covers long-term care. I explore alternative reasons for failure to purchase coverage by well-informed, expected utility-maximizing risk-averse individuals for whom LTC is associated with a large increase in mortality and for whom family members represent an alternative source of care. There may be no demand for LTC insurance even if it is made available at actuarially fair premiums because the main consequence of coverage is to enhance the expected value of one's estate.